The Concept of Muhasabah in the Thought of Imam Al-Ghazali and its Relevance to the Moral Development of Generation Z in the Society 5.0 Era - Muhammad Ichsan Thaib; Abd.Rajak; Hayati; Abdul Hadi (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
The era of Society 5.0, integrating cyberspace and physical space, has created a paradox for Generation Z, wherein heightened digital connectivity coincides with increased vulnerability to moral degradation and identity crises. This study aims to examine the concept of muhasabah in the thought of Imam Al-Ghazali and assess its relevance for moral development among Generation Z. Employing library research, the study analyzed primary sources, including Ihya' 'Ulumuddin and other works of Al-Ghazali, alongside secondary literature comprising books and journal articles. Data were analyzed using qualitative content analysis with a hermeneutic approach to connect Al-Ghazali’s classical insights with contemporary contexts. The results reveal that muhasabah constitutes a holistic spiritual discipline structured through the quartet system of musyaratah, muraqabah, muhasabah, and mu’aqabah, encompassing both evaluation of external actions and internal thought trajectories. Generation Z faces multidimensional moral challenges that create a significant gap between digital literacy and moral resilience. Al-Ghazali’s muhasabah is identified as a counter-hegemonic spiritual technology, functioning as a framework for self-management, mental filtering, cognitive-spiritual therapy, and self-liberation from algorithmic influence. Implementing muhasabah in character education requires transforming the curriculum toward introspective training, developing digital mindfulness modules, and establishing a collective reflective ecosystem involving educators, families, and communities. These findings are operationalized in the “Schools and Families with Muhasabah” program, combining reflective practices at school and home supported by the My Spiritual Tracker application. Collectively, this study demonstrates that muhasabah can enhance ethical awareness, resilience, and reflective capacity, equipping Generation Z to navigate the moral complexities of the Society 5.0 era.